Children of the Dust Bowl: The True Story of the School at Weed Patch Camp - Stanley, Jerry, 1941- (New York : Crown, 1992)
Describes the plight of the migrant workers who traveled from the Dust Bowl to California during the Depression and were forced to live in a federal labor camp and discusses the school that was built for their children.
Includes bibliographical references (p. 78-80) and index.
Keywords: Children of migrant laborers -- Education -- 20th century -- California; Droughts -- History -- 20th century -- Southwestern States; Depressions -- Juvenile literature. -- 1929 -- Great Plains; Depressions -- Juvenile literature. -- 1929 -- Southwestern States; Migrant labor -- California; Depressions -- 1929; Depressions, Economic; United States -- Social conditions